Hsp90 and hepatobiliary transformation during sea lamprey metamorphosis. Issue 1 (December 2015) - Chung-Davidson, Yu-Wen; Yeh, Chu-Yin; Bussy, Ugo; Li, Ke; Davidson, Peter; Nanlohy, Kaben; Brown, C.; Whyard, Steven; Li, Weiming
Abstract Background Biliary atresia (BA) is a human infant disease with inflammatory fibrous obstructions in the bile ducts and is the most common cause for pediatric liver transplantation. In contrast, the sea lamprey undergoes developmental BA with transient cholestasis and fibrosis during metamorphosis, but emerges as a fecund adult. Therefore, sea lamprey liver metamorphosis may serve as an etiological model for human BA and provide pivotal information for hepatobiliary transformation and possible therapeutics. Results We hypothesized that liver metamorphosis in sea lamprey is due to transcriptional reprogramming that dictates cellular remodeling during metamorphosis. We determined global gene expressions in liver at several metamorphic landmark stages by integrating mRNA-Seq and gene ontology analyses, and validated the results with real-time quantitative PCR, histological and immunohistochemical staining. These analyses revealed that gene expressions of protein folding chaperones, membrane transporters and extracellular matrices were altered and shifted during liver metamorphosis. HSP90, important in protein folding and invertebrate metamorphosis, was identified as a candidate key factor during liver metamorphosis in sea lamprey. Blocking HSP90 with geldanamycin facilitated liver metamorphosis and decreased the gene expressions of the rate limiting enzyme for cholesterol biosynthesis, HMGCoA reductase (hmgcr ), and bile acid biosynthesis, cyp7a1 . Injection ofhsp90 siRNA for 4 days altered gene expressions ofmet, hmgcr, cyp27a1, andslc10a1 . Bile acid concentrations were increased while bile duct and gall bladder degeneration was facilitated and synchronized afterhsp90 siRNA injection. Conclusions HSP90 appears to play crucial roles in hepatobiliary transformation during sea lamprey metamorphosis. Sea lamprey is a useful animal model to study postembryonic development and mechanisms forhsp90 -induced hepatobiliary transformation.